Becoming The Self on A Divorce Woman - Deny Surya Saputra; Regina Navira Pratiwi; Ika Wahyu Pratiwi (Jurnal Perempuan dan Anak, 2022)
Based on the experience of researchers as counselors in dealing with women's life problems, one of the problems experienced by women is divorce that occurs because they are considered to be a person who can be humiliated, not allowed to work, isolated from home affairs and child care without regard to his personal needs as a woman , and other treatments that are considered and felt to be unfair to a woman. That experience makes them forced to divorce and continue their lives by striving to be a person who does everything normal men do, such as working and participating in the social world. The purpose of this study is to find out the description of women's behavior in an attempt to become a self (becoming the self) in the midst of the divorce issues they experienced through four women who had experienced divorce as a sample in this study. The research method used in this study is a descriptive qualitative method that will provide a complete picture of the process of women in their efforts to become themselves. The results showed that women who are engaged in their efforts to become the self are women who want gender equality through several ways, namely by working and actively participating in social activities or social organizations.   Keyword: woman, divorce woman, the self